Evaluation of changes in egg yolk lipids during storage based on lipidomics through UPLC-MS/MS. (1st January 2023) - Liu, Yu; Guo, Xin; Wang, Niannian; Lu, Shiling; Dong, Juan; Qi, Zeliang; Zhou, Junrong; Wang, Qingling
Highlights: Lipidomics was used to identify lipid changes during the storage of egg yolk. 159 different lipid species were screened out to evaluate the egg storage. The lipidomics profile of egg yolk changed most significantly when stored to 21 days. Glycerophospholipid and glycerolipid metabolism are pivotal metabolic pathways. Abstract: A comprehensive UPLC-MS/MS-based lipidomics analysis of egg yolk at different storage periods was performed. Through the analysis, 836 lipid species from 27 subclasses were detected, including 159 significantly different lipid species. Glycerolipids (GL) and glycerophospholipids (GP) were the most abundant lipids, followed by fatty acyls (FA), sphingolipids (SP), sterol lipids (ST), and prenol lipids (PR). PCA and OPLS-DA showed that egg yolk lipids changed significantly with prolonged storage. Moreover, glycerophospholipid metabolism and glycerolipid metabolism were key metabolic pathways, as phosphatidic acid (PA), lysophosphatidic acid (LPA), and diglyceride (DG) were key lipid metabolites in the related metabolic pathways of egg yolk during storage. Furthermore, egg yolk quality changed the most when stored up to 21 days. Our study establishes a foundation for the quality control and the lipid oxidation mechanism of eggs during storage.